Pengaruh Pemberdayaan Terhadap Kinerja Pegawai Melalui Organizational Citizenship Behavior - Alfarizki, Nur Huda (Magister Manajemen Universitas Wisnuwardhana, 2023)
Abstract. The purpose of the study to examine the role of OCB in mediating the effect of employee empowerment on employee performance at PT. Wijaya Karya (Persero) Tbk, infra 2, Department 4 Surabaya. The population of this study is employees of PT. Wijaya Karya (Persero) Tbk, infra 2, Department 4 Surabaya totaling 30 employees. A sample is a portion of a population that has relatively similar characteristics and is considered to be representative of the population (Singarimbun, 1991). The sampling technique in this study uses a census, where the samples used are all members of the existing population. So that the sample in the study was 30 employees. The analysis technique used is path analysis. The results of the study explain that empowerment affects Organizational Citizenship Behavior and organizational performance is acceptable. Organizational Citizenship Behavior affects employee performance is acceptable. Organizational Citizenship Behavior can mediate the effect of empowerment on employee performance